Implementasi Produk Asuransi Syariah "Prucinta" pada Bank Syariah Indonesia - Herawan, Muhammad Hafiz; Wirianisa, Syifani (IDARI: Jurnal Manajemen Dakwah, 2025)
This study observes PruCinta, a sharia-based life insurance product offered by Bank Syariah Indonesia (BSI) in collaboration with Prudential Indonesia. The purpose is to understand the product's operational model, analyze its strengths and weaknesses, and identify its benefits for Muslim customers seeking ethical financial protection. The method used includes field observation at BSI KCP Kemanggisan, literature review, and interviews with staff. Findings indicate that PruCinta adheres to Islamic contracts such as Tabarru' and Wakalah bil Ujrah, ensuring ethical fund management and solidarity among participants. Key advantages include digital accessibility, premium flexibility, and professional fund management. However, challenges remain in public awareness and the cost structure compared to conventional insurance. This paper concludes that PruCinta is a strategic financial product that offers life protection with added spiritual value in accordance with Islamic principles.